PAPAYA SEED EXTRACT ON WOUND RECUPERATING - Meliana Nursihhah (Perhimpunan Kesehatan Holistik Indonesia, 2021)
Papaya has extraordinary benefits counting to encourage the stomach related framework, as a source of cancer prevention agents, and indeed able to operate as anti-fungal and anti-bacterial. Papaya seeds are known to contain different compounds such as tocophenols, terpenoids, flavonoids, alkaloids such as carpain, and different chemicals such as papain proteins, chymoprotein proteins, and lysozyme. Papaya natural product is compelling in avoiding necrotic burn disease, solidifying of the wound surface and thickening of the skin